Anaphylaxis Simulation - Christopher Eric McCoy (eScholarship Publishing, University of California, 2017)
Audience: This simulation-based scenario is appropriate for medical students and emergency medicine residents at any level of training. Introduction: Anaphylaxis is an acute, severe, systemic allergic reaction that is potentially life threatening. The epidemiological characteristics of anaphylaxis are not entirely accurate secondary to underreporting and misdiagnosis. Estimates of lifetime prevalence range from 0.05% to 2%, with rates up to 15% described in the literature, 2% of which have fatal episodes. The incidence is estimated at 0.03% to 0.95%, with 0.002% fatal episodes annually (~1500 annual deaths in the United States). Although described more than 100 years ago, only recently has a definition been described that provides the clinician with specific criteria for diagnosis in the clinical setting. The National Institute of Allergy and Infectious Disease (NIAID) and Food Allergy and Anaphylaxis Network (FAAN) convened a symposium that included representatives from 16 different organizations (including emergency medicine) to establish clinical criteria that would accurately identify cases of anaphylaxis. Anaphylaxis is a true medical emergency. Rapid identification and management of this condition plays a major role in patient prognosis. Objectives: By the end of this simulation-based session, the learner will be able to: 1) Recognize and diagnose anaphylaxis according to the criteria set forth by the NIAID and FAAN symposium 2) discuss the appropriate dose, concentration, and delivery route of epinephrine for anaphylaxis 3) list and discuss the rationale for the second-line therapeutic options used to treat anaphylaxis, and 4) develop an appropriate disposition algorithm to be used when managing anaphylaxis in the clinical setting. Method: This educational session is a high-fidelity simulation.